EFFECTS OF NICKEL-CHROME DENTAL ALLOYS USED IN DENTISTRY ON SALIVA AND SERUM NICKEL LEVELS, PERIPHERAL LYMPHOCYTE-T AND SOME OTHER BLOOD PARAMETERS - (:unkn) unknown (WILEY, 1992)
Epidemiological investigations have shown that nickel is a potent sensitivity producing agent. However, it is not known if intra-oral use of nickel-chrome alloys can cause any sensitization reaction. The purpose of this study was to determine if nickel-chrome alloys used in dentistry influence nickel levels in saliva and serum and whether there were associated changes of some blood parameters such as lymphocyte, T-lymphocyte, neutrophil. eosinophil, basophil and monocyte. The study was performed on 10 patients all of whom had no medical and dental history of using nickel containing drugs or restorations. Four unit fixed partial prostheses containing 22-97% nickel and 22.65% chrome were constructed and worn by the patients. Blood and unstimulated whole saliva samples were taken from the patients before insertion of the prostheses and then 1 month and 6 months post-insertion. Hematocrit determinations, total and differential leucocyte count, total T-lymphocyte counts and serum nickel concentrations were determined from the blood samples and salivary nickel concentrations from the saliva samples. It was found that there were no significant changes in circulating T-lymphocyte and monocyte population but a decrease was found in circulating eosinophil and an increase in circulating neutrophil and basophil populations.